Proceedings of the ACM SIGAda Annual International Conference on Ada and Related Technologies 2009
DOI: 10.1145/1647420.1647435
|View full text |Cite
|
Sign up to set email alerts
|

Validate, simulate, and implement ARINC653 systems using the AADL

Abstract: Safety-critical systems are widely used in different domains and lead to an increasing complexity. Such systems rely on specific services such space and time isolation as in the ARINC653 avionics standard. Their criticality requires a carefully driven design based on an appropriate development process and dedicated tools to detect and avoid problems as early as possible.Model Driven Engineering (MDE) approaches are now considered as valuable approach for building safety-critical systems. The Architecture Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…In addition, some research work have focused on extending the language using these extension mechanisms or investigating alternative ways. The most close research works to ours from this perspective are reported in [20] and [21]. Delange et al [20], present an approach based on AADL, which covers the modeling, verification and implementation of ARINC653 systems.…”
Section: Related Workmentioning
confidence: 97%
“…In addition, some research work have focused on extending the language using these extension mechanisms or investigating alternative ways. The most close research works to ours from this perspective are reported in [20] and [21]. Delange et al [20], present an approach based on AADL, which covers the modeling, verification and implementation of ARINC653 systems.…”
Section: Related Workmentioning
confidence: 97%
“…Similarly, there are many systemsoftware solutions for avionics, including POK [17] and XtratuM [18]. However, all these systems support either AUTOSAR or ARINC, but not both.…”
Section: Related Workmentioning
confidence: 99%
“…This Ada subset allows programmers to write Ada programs that are compliant with real-time critical systems requirements. Delange et al [14] define guidelines for the implementation of ARINC653 systems using AADL. This ARINC653 guidelines specifies a subset of AADL to model all the concepts of an ARINC 653 architecture.…”
Section: Related Workmentioning
confidence: 99%